Implementing Comprehensive Primary Care Referral Tracking in a Patient-Centered Medical Home. Issue 3 (July 2018) - Spahr, Jenny; Coddington, Jennifer; Edwards, Nancy; McComb, Sara
Abstract : The Patient-Centered Medical Home care model emphasizes efficient, coordinated care distributed among interdisciplinary team members. One key function to care coordination is referral/test tracking. This study evaluated the referral practices in a nurse-managed Patient-Centered Medical Home primary care clinic. The major findings corroborate the need for a well-organized referral-tracking system that is centralized and contains safety nets to reduce the number of delayed or missed referrals. Abstract : Supplemental Digital Content is Available in the Text.